A característica de Euler de superfície - VELASCO, Brenda Letícia Noronha (2023)
This work aims to explore the Euler characteristic of polyhedra, surfaces and connected sums of surfaces. Initially, the proof of Euler’s theorem for convex polyhedra due to the mathematician Adrien-Marie Legendre will be presented. Then, the concept of regular surface is discussed and we present the examples of the Sphere and the Torus. In addition, the study also addresses the triangulation of surfaces and the Euler characteristic of a triangulation and connected sums of surfaces.